Energy Accumulation by Hydrogen Technologies - Jiřina Čermáková; Aleš Doucek; Lukáš Polák (Acta Polytechnica, 2012)
Photovoltaic power plants as a renewable energy source have been receiving rapidly growing attention in the Czech Republic and in the other EU countries. This rapid development of photovoltaic sources is having a negative effect on the electricity power system control, because they depend on the weather conditions and provide a variable and unreliable supply of electric power. One way to reduce this effect is by accumulating electricity in hydrogen. The aim of this paper is to introduce hydrogen as a tool for regulating photovoltaic energy in island mode. A configuration has been designed for connecting households with the photovoltaic hybrid system, and a simulation model has been made in order to check the validity of this system. The simulation results provide energy flows and have been used for optimal sizing of real devices. An appropriate system can deliver energy in a stand-alone installation.